Total Synthesis of Diterpenoid Steenkrotin A1. (20th April 2015) - Pan, Saiyong; Xuan, Jun; Gao, Beiling; Zhu, An; Ding, Hanfeng
Abstract: A concise and diastereoselective total synthesis of the diterpenoid (±)‐steenkrotin A is described for the first time. The strategy mainly features three key ring formations: 1) a rhodium‐catalyzed OH bond insertion followed by an intramolecular carbonyl‐ene reaction to build up the tetrahydrofuran subunit; 2) sequential SmI2 ‐mediated Ueno–Stork and ketyl–olefin cyclizations to construct the [5, 7] spirobicyclic skeleton; and 3) an intramolecular aldol condensation/vinylogous retro‐aldol/aldol sequence to form the final six‐membered ring with inversion of the relative configuration at the C7 position.